Complete genome sequence of Lysinibacillus sp. strain SGAir0095, isolated from tropical air samples collected in Singapore - Wong, Anthony (2020)
Lysinibacillus sp. strain SGAir0095 was isolated from tropical air samples collected in Singapore, and its complete genome was sequenced with a hybrid strategy using single-molecule real-time sequencing and short reads. The genome consists of one chromosome of 4.14 Mbp and encompasses 3,885 protein-coding genes, 39 rRNAs, and 101 tRNAs.